Abnormal Cerebrospinal Fluid Biochemistry in Biotinidase Deficiency Causing Diagnostic Conundrum. (January 2014) - Krishnakumar, Deepa; Maw, Anna; Brown, Richard; Hogg, Sarah; Calvin, Jackie; Parker, Alasdair P. J.
Biotinidase deficiency is a treatable cause of infantile epilepsy and the presentation can be nonspecific. The seizures are difficult to differentiate from other causes of epileptic encephalopathy, which generally have a poor prognosis. We report 2 infants who presented with seizures, and whose low cerebrospinal fluid glucose and high cerebrospinal lactate caused a diagnostic dilemma. Subsequent urine organic acids pointed to the correct diagnosis and avoided invasive investigation. The children had a good clinical outcome with resolution of their seizures on biotin treatment.